Answer:
The explanation of how the figure illustrates that 6(9) = 6(4) + 6(5) is below.
![6* 9 = 6* 4 +6* 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gkzr1mko54faeka4qbladdqudy7twwk5hk.png)
Explanation:
Consider a Rectangle ABCD segregate in two Rectangle by a Dash Line
i.e Rectangle AEFD and
Rectangle EBCF
We Know
![\textrm{Area of Rectangle}=Length* Width](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gvueagdymo5r2qq7tv59dwcfo87i7gmmlg.png)
For Rectangle ABCD we have
Length = 6
Width = 9
..........( 1 )
So For Rectangle AEFD we have
Length = 6
Width = 4
..........( 2 )
Similarly, For Rectangle EBCF we have
Length = 6
Width = 5
..........( 3 )
Now,
![\textrm{Area of Rectangle ABCD}=\textrm{Area of Rectangle AEFD}+\textrm{Area of Rectangle EBCF}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ifvnpqj8d8vhekzj6w31vmgxoy17ft5x1w.png)
Substituting the values we get
![6* 9 = 6* 4 +6* 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gkzr1mko54faeka4qbladdqudy7twwk5hk.png)
Which is equal to
So, 6(9) = 6(4) + 6(5).